2023
DOI: 10.1155/2023/5225872
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Medical Students: Harnessing Artificial Intelligence for Precision Point-of-Care Echocardiography Assessment of Left Ventricular Ejection Fraction

Ziv Dadon,
Amir Orlev,
Adi Butnaru
et al.

Abstract: Introduction. Point-of-care ultrasound (POCUS) use is now universal among nonexperts. Artificial intelligence (AI) is currently employed by nonexperts in various imaging modalities to assist in diagnosis and decision making. Aim. To evaluate the diagnostic accuracy of POCUS, operated by medical students with the assistance of an AI-based tool for assessing the left ventricular ejection fraction (LVEF) of patients admitted to a cardiology department. Methods. Eight students underwent a 6-hour didactic and hands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In alignment with much of the existing literature in the field, our previous article tested the feasibility and accuracy of this AI-based tool, focusing on the clinical validation of the given algorithms [31]. This initial validation step is important to verify the absence of biases in the datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In alignment with much of the existing literature in the field, our previous article tested the feasibility and accuracy of this AI-based tool, focusing on the clinical validation of the given algorithms [31]. This initial validation step is important to verify the absence of biases in the datasets.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective study, we showed that medical students with basic image acquisition skills who used a HUD with an automated proprietary AI program to assess LVEF, were able to achieve a degree of accuracy that was similar to that of board-certified cardiologists [31]. This present study is a continuation of this project with the objective of determining the ability of the HUD AI-based tool in the hands of novice users to predict outcomes of patients admitted to the cardiology department.…”
Section: Introductionmentioning
confidence: 91%